2006
DOI: 10.1345/aph.1e658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glucosamine on Glucose Control

Abstract: Small, short-term studies suggest that glucosamine may be used in selected patients without affecting glucose control; however, data in patients with diabetes mellitus are limited, and close monitoring for potential changes in glucose control is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…В доступной нам научной литературе имеются выводы о значительной эффективно-сти оригинального кристаллического ГС в препарате ДОНА, который успеш-но применяется при первичном и вторичном ОА различной локализа-ции, спондилоартрозе, достоверно уменьшая суставную боль, обладая противовоспалительным действием. Хорошая переносимость препарата позволяет рекомендовать его для использования в реальной клиниче-ской практике, для улучшения каче-ства жизни пациентов с ОА [9,11,14,15,17,19,23,28,31]. Хотелось бы сослаться на личный опыт использования ДОНА -ориги-нального кристаллического ГС, кото-рый назначался для лечения ОА больным, находившимся на стацио-нарном лечении в ревматологиче-ском отделении НУЗ «Дорожная клиническая больница на станции Воронеж-1 ОАО «РЖД».…”
Section: оценивая эффективность дона следует отметить что кгс принаunclassified
“…В доступной нам научной литературе имеются выводы о значительной эффективно-сти оригинального кристаллического ГС в препарате ДОНА, который успеш-но применяется при первичном и вторичном ОА различной локализа-ции, спондилоартрозе, достоверно уменьшая суставную боль, обладая противовоспалительным действием. Хорошая переносимость препарата позволяет рекомендовать его для использования в реальной клиниче-ской практике, для улучшения каче-ства жизни пациентов с ОА [9,11,14,15,17,19,23,28,31]. Хотелось бы сослаться на личный опыт использования ДОНА -ориги-нального кристаллического ГС, кото-рый назначался для лечения ОА больным, находившимся на стацио-нарном лечении в ревматологиче-ском отделении НУЗ «Дорожная клиническая больница на станции Воронеж-1 ОАО «РЖД».…”
Section: оценивая эффективность дона следует отметить что кгс принаunclassified
“…Glucosamine is presently in wide use because of its purported beneficial effects in patients with osteoarthritis. Alterations in glucose control have not been documented in trials of short duration exercises conducted in healthy or diabetic participants [17]. It is important to consider glucosamine effect on glucose metabolism, especially when being used in conjunction with exercise therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Issues are being raised about the possibility of glucosamine interfering with blood glucose control. A recent review of the literature on this topic concluded that although alterations in glucose metabolism that have been noted in animals gave high glucosamine, similar effects have not been consistently documented in humans following usual oral doses [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] However, other human studies having investigated shortterm intravenous glucosamine infusion effects did not report any such adverse impacts on either insulin sensitivity or glucose level. 9,10 Few studies aiming to evaluate the effects of oral standard doses of glucosamine in healthy humans concluded that oral glucosamine did not induce insulin resistance, [11][12][13] these findings add fuel to the controversy of whether glucosamine can adversely affect glucose metabolism. In this study, we aimed to determine the effects of oral glucosamine on glucose metabolism and insulin resistance in non-diabetic patients with OA in Northeastern Iran.…”
mentioning
confidence: 99%